2018
DOI: 10.1097/mao.0000000000001961
|View full text |Cite
|
Sign up to set email alerts
|

Patient Positioning During In-Office Otologic Procedures Impacts Physician Ergonomics

Abstract: Placing patients in a supine position for cerumen removal results in more favorable ergonomic positioning for the physician, thus reducing risk for work-related musculoskeletal disorders. This suggests that physicians should consider placing patients in the supine position for in-office otologic procedures. Further study is needed to investigate optimal ergonomic positioning for other common otolaryngology procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…(2017 and 2018) looked to measure Rapid Upper Limb Assessment scores by observing joint positions of clinicians while performing cerumen removal using a wall-mounted microscope. 35,36 The authors showed a reduction of 2.0 points ( p < 0.05) on the Rapid Upper Limb Assessment scoring system in their first study when mock patients were supine versus sitting, and one year later demonstrated a similar reduction of 2.5 points ( p < 0.05) in another study involving 24 genuine patients.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…(2017 and 2018) looked to measure Rapid Upper Limb Assessment scores by observing joint positions of clinicians while performing cerumen removal using a wall-mounted microscope. 35,36 The authors showed a reduction of 2.0 points ( p < 0.05) on the Rapid Upper Limb Assessment scoring system in their first study when mock patients were supine versus sitting, and one year later demonstrated a similar reduction of 2.5 points ( p < 0.05) in another study involving 24 genuine patients.…”
Section: Resultsmentioning
confidence: 91%
“…For instance, Govil et al (2018) used an observer in the room at the time of procedure whereas Smith et al (2015) measure data from static photography taken at the end of each simulated test session. 36,37 The resulting Rapid Upper Limb Assessment score may be affected by the angle and aspect of the relevant photograph, which limits the generalisability of Rapid Upper Limb Assessment scores measured in different ways across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[191] 2019 Iran Assessment using RULA of workers performing a task in a traditional way and with a newly designed instrument. [192] 2018 USA Application of RULA on otolaryngologists. [193] 2018 Ireland Use of RULA and other tools on ICU nurses.…”
Section: Human Health and Social Work Activitiesmentioning
confidence: 99%
“…• Otolaryngology Goyil et al [192,199] analysed the postures adopted by the otolaryngologists when the patient was placed in position (sitting or lying on their back). The RULA method was used.…”
Section: • Radiologymentioning
confidence: 99%